Echinacea/sage or chlorhexidine/lidocaine for treating acute sore throats: a randomized double-blind trial - Schapowal A; Berger D; Klein P; Suter A (European Journal of Medical Research, 2009)
Abstract Background The aim of this trial was to assess the relative efficacy of a sage/echinacea spray and a chlorhexidine/lidocaine spray in the treatment of acute sore throats. Methods This was a multicenter, randomized, double-blind, double-dummy controlled trial carried out in eleven general practices in Switzerland. A total of 154 patients (133 analyzed in per protocol collective) at least 12 years old with acute sore throat present for not more than 72 hours prior to inclusion and with a throat score ≥6 participated in the study. They used either an echinacea/sage spray or a chlorhexidine/lidocaine spray with two puffs every 2 hours, in a double-dummy blinded manner, up to 10 times daily until they were symptom-free, for a maximum of 5 days. The main outcome measures was the comparison of response rates during the first three days. A response was defined as a decrease of at least 50% of the total symptoms compared to baseline. Results The echinacea/sage treatment exhibited similar efficacy to the chlorhexidine/lidocaine treatment in reducing sore throat symptoms during the first 3 days (P(x < Y) = .5083). Response rates after 3 days were 63.8% in the echinacea/sage group and 57.8% in the chlorhexidine/lidocaine group. For all secondary parameters, such as time to becoming symptom free, throat pain, and global assessments of efficacy by the physician and patient, no difference between the two treatments was seen. They were both very well tolerated. Conclusion An echinacea/sage preparation is as efficacious and well tolerated as a chlorhexidine/lidocaine spray in the treatment of acute sore throats.